2020
DOI: 10.1186/s12987-020-00218-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive measurement of choroid plexus apparent blood flow with arterial spin labeling

Abstract: Background The choroid plexus is a major contributor to the generation of cerebrospinal fluid (CSF) and the maintenance of its electrolyte and metabolite balance. Here, we sought to characterize the blood flow dynamics of the choroid plexus using arterial spin labeling (ASL) MRI to establish ASL as a non-invasive tool for choroid plexus function and disease studies. Methods Seven healthy volunteers were imaged on a 3T MR scanner. ASL images were acquired with 12 labeling durations and post labeling delays. R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 60 publications
2
28
0
Order By: Relevance
“…A similar protocol has recently been applied in healthy adults and has demonstrated that arterial arrival to the CP is 1.24 AE 0.2 s, T 1 of the CP is 2.33 AE 0.30 s, and apparent CP perfusion is 39.5 ml/100 g/min. 27 Our perfusion values from this study and our previous study 4 are in good agreement with this perfusion value. It should be noted that arrival time and T 1 of the CP is longer than for cortex.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…A similar protocol has recently been applied in healthy adults and has demonstrated that arterial arrival to the CP is 1.24 AE 0.2 s, T 1 of the CP is 2.33 AE 0.30 s, and apparent CP perfusion is 39.5 ml/100 g/min. 27 Our perfusion values from this study and our previous study 4 are in good agreement with this perfusion value. It should be noted that arrival time and T 1 of the CP is longer than for cortex.…”
Section: Discussionsupporting
confidence: 91%
“…It should also be noted that as the CP is a relatively small structure, partial volume effects with CSF or periventricular tissue may also affect measurements and lead to an underestimation of true CP perfusion. 27 To reduce this concern we segmented the CP manually on T 1 -weighted images, however, given the inherent lower spatial resolution of pCASL some partial volume contributions will persist, but are expected to be similar in all participants. The extent of atrophy, and associated size of the lateral ventricles, may influence the ability to accurately segment the CP and as such the measured CP perfusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evans et al [49] recently described using magnetic resonance imaging (MRI) to measure the movement of water from arterial blood to CSF in human brain as well as mouse. MRI was also used by Zhao et al [50] to examine CP hemodynamic parameters (flow, transit time) in humans. Eide et al [51] used MRI to track the clearance of gadobutrol after intrathecal administration in healthy individuals and those with idiopathic normal pressure hydrocephalus.…”
Section: Choroid Plexusmentioning
confidence: 99%